2015
DOI: 10.1002/chem.201502910
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and β‐Alkylation of Alcohols Catalysed by Iridium(I) Complexes with Functionalised N‐Heterocyclic Carbene Ligands

Abstract: The borrowing hydrogen methodology allows for the use of alcohols as alkylating agents for CC bond forming processes offering significant environmental benefits over traditional approaches. Iridium(I)-cyclooctadiene complexes having a NHC ligand with a O- or N-functionalised wingtip efficiently catalysed the oxidation and β-alkylation of secondary alcohols with primary alcohols in the presence of a base. The cationic complex [Ir(NCCH3 )(cod)(MeIm(2- methoxybenzyl))][BF4 ] (cod=1,5-cyclooctadiene, MeIm=1-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 123 publications
2
47
0
Order By: Relevance
“…In order to gain insight on the catalyst mode of action, a detailed mass spectrometric studies were performed. In particular, a proposed mechanism consisting of two catalytic cycles working in tandem is outlined in Scheme , based on previously reported mechanism for the transfer hydrogenation of ketones, and α,β‐unsaturated ketones ,,. In particular, in the first catalytic cycle, the reaction of Ir‐NHC complex ( 1 e ) in presence of i ‐PrOH would give an i ‐propoxy bound Ir‐NHC species ( A ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to gain insight on the catalyst mode of action, a detailed mass spectrometric studies were performed. In particular, a proposed mechanism consisting of two catalytic cycles working in tandem is outlined in Scheme , based on previously reported mechanism for the transfer hydrogenation of ketones, and α,β‐unsaturated ketones ,,. In particular, in the first catalytic cycle, the reaction of Ir‐NHC complex ( 1 e ) in presence of i ‐PrOH would give an i ‐propoxy bound Ir‐NHC species ( A ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the products were identified according to commercially available samples: 1‐phenylethanol, cyclohexanol, α‐methyl‐2‐naphtalenemethanol, 4‐bromo‐α‐methylbenzyl alcohol, 4‐methoxy‐α‐methylbenzyl alcohol and N ‐benzylaniline. The spectroscopic features of 1‐phenylhexan‐1‐ol were obtained from the literature …”
Section: Methodsmentioning
confidence: 99%
“…Most of the traditional C−C coupling protocols suffer from the production of stoichiometric amounts of waste salts, whereas the catalytic one‐pot acceptorless dehydrogenation of alcohols to the corresponding carbonyl compounds followed by aldol condensation and hydrogenation in one pot (so‐named Guerbet reaction, Scheme ) represents a more elegant way to form new carbon–carbon bonds . During the last decade, it has been demonstrated that different functionalized alcohols can be used as green alkylating agents, mainly upon ruthenium, iridium, and rhenium catalysis …”
Section: Overview Of Recent Advances In Chemospecific One‐pot Transfmentioning
confidence: 99%